A report on practice in industry training in fish processing technology. - Kampitan, Ma. Cristina R. (College of Fisheries, University of the Philippines, 1980)
Manila bay ranks third among the many rich fishing areas around in the Philippines. Its bottom topography is generally flat, muddy or sandy for trawling operations. Despite these facts many fishermen had noted that catch per unit effort had shown an undesirable decrease. However, this undesirable could be attributed to over fishing of hundred baby trawlers found in this area. Most of the baby trawlers come from Malabon and Navotas. These baby trawlers set out early in the morning and comeback just in time for marketing which is usually late in the afternoon. If they're lucky for that day's trip in a way that the sea is calm, they usually covered the area of Corregidor, Cavite or Bataan. But if the weather does not permit, they're back at the port by noon thereby incurring losses for the day's trip or gain which id below average.